Remote Sensing Of Turbidity Mapping From Digital Camera Imagery. - Al Sultan, Sultan; H., S. Lim; MatJafri, M. Z.; Abdullah, K.; A. Bakar, M. N. (2004)
A complete set of normal digital camera data and ground-based measurements are used to test an algorithm for retrieval of turbidity distribution in the Prai Estuary, Penang, Malaysia.